Non-ST segment elevation myocardial infarction: results of 2021−2022 - O. L. Barbarash; V. V. Kashtalap (Фундаментальная и клиническая медицина, 2023)
Here we provide a brief overview of current consensus documents and clinical guidelines concerning the management of the patients with acute coronary syndrome (ACS) without ST segment elevation, which have been released in 2021-2022. Further, we consider statistics on ACS in the Russian Federation and discuss an expert analysis of the effects of COVID-19 pandemic on ACS-associated healthcare in Russian Federation, as well as the pathological effects of SARS-CoV-2 on the circulatory system. The fourth universal definition of myocardial infarction (2018) is also clarified according to the recent updates.